2015
DOI: 10.5539/jas.v7n8p131
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequence Characteristics and Phylogenetics of Putative Imprinted Genes on Bovine Chromosome 29

Abstract: Cattle are important livestock species with huge genetic resource for food security, agriculture and livelihoods. Over 60% of its genes are homologous to all mammalian species which creates a molecular basis for conducting comparative genomic analysis. Genomic imprinting has been implicated in a variety of biological functions and so identification of new or verification of known imprinted genes in livestock species is of high agricultural and biomedical importance. Fourteen (14) putative imprinted genes on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This is consistent with the associated molecular functions of the respective genes [17]. The presence of the protein kinases (cAMP, PKC, CK2) involved in glycogen regulation, muscle development and cellular regulation earlier reported by Bamidele et al [3] to be found in TSSC4, PHLDA2 and NAP1L4, could also explain the up-regulation of the respective gene transcripts in the muscle tissue system. This is in contrast to that observed in KCNQ1 and CDKN1C wherein no protein kinases were earlier found and whose transcripts were only upregulated in the nervous and secretory tissue systems respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with the associated molecular functions of the respective genes [17]. The presence of the protein kinases (cAMP, PKC, CK2) involved in glycogen regulation, muscle development and cellular regulation earlier reported by Bamidele et al [3] to be found in TSSC4, PHLDA2 and NAP1L4, could also explain the up-regulation of the respective gene transcripts in the muscle tissue system. This is in contrast to that observed in KCNQ1 and CDKN1C wherein no protein kinases were earlier found and whose transcripts were only upregulated in the nervous and secretory tissue systems respectively.…”
Section: Discussionsupporting
confidence: 89%
“…have also been reported to be actively involved in the complex regulatory system [21]- [23]. Two of these regulators (SOX and CK2) have been reportedly identified in NAP1L4 gene [3] which according to Busca and Balotti [22], play a significant role in the regulation of melanogenesis. Several studies in human and mice have reported that the inhibition of the CK2 is specifically linked to variations in skin pigmentations [24] [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation